A new configuration of the Spanish cultural field after the feminist tsunami: an approach to some discursive consequences of March 8, 2018 (Altre Modernità, 2025)
The event of March 8, 2018, crystallized a feminist social movement that had been brewing for years. The demonstration and strike led by women that year forced society to reexamine the principles of supposed equality on which it was being built. This article proposes a review of the cultural productions that emerged in the heat of that reflection, both those that champion new feminist advances and positions and those that revive figures and texts they call feminist, even though they are not in reality. Forced readings of these proposals represent a serious danger for feminist thought by conflating criteria that can lead to the neutralization of the most combative feminism. Through different examples, these positions will be analyzed to propose the need for courageous and objective interpretations that move away from a superficial vindication of supposed cultural products as feminist when they are far from this position.
Keywords: March 8, 2018; feminist literature; non-feminist authors; analysis of cultural production